Bunuel wrote:

Is \(\frac{x}{p}(p^2 + q^2 + r^2) = xp + yq + zr\) ?

(1) \(yq = r^2\) and \(zr = q^2\)

(2) \(x = p\)

We'll go for a Precise approach of simplification since this looks like a very technical question.

Multiplying by p (p cannot be zero as it is in denominator) gives:

\(xp^2 + xq^2 + xr^2 = xp^2 + yqp + zrp\). Cancelling common factors and changing sides gives:

\(xq^2 - yqp + xr^2 - rzp = 0\)

Substituting the equations in (1) gives \(xzr - yqp + xyq - zrp = zr(x - p) + yq(x - p) = (zr + yq)(x-p)\)

Without knowing if \(zr + yq = 0\) or if \(p = x\) we cannot know if this is 0.

Insufficient!

Substituting the equations in (2) gives

\(xq^2 - yqx + xr^2 - rzx = x(q^2 - yq + r^2 - rz)\)

Since we don't know if either side is 0, this is also insufficient.

But, if we substitute \(x = p\) into our result from (1) we get a result of 0!

This means that the original equation is true.

(C) is our answer.

_________________

David

Senior tutor at examPAL

Signup for a free GMAT course

We won some awards:

Save up to $250 on examPAL packages (special for GMAT Club members)